2015
DOI: 10.3109/14767058.2015.1114085
|View full text |Cite
|
Sign up to set email alerts
|

The association of HLA-G and immune markers in recurrent miscarriages

Abstract: The CD56 expression of uterine NK cells may be an indicator of a HP. However, not statistically significant, the increased expression of CD16, CD8, and also significantly increased expression of TNF may be associated with the predominant cytotoxic activity in the maternal immune system in patients with RM. Although there was no change in the expression of HLA-G, this finding may mean that the maternal immune system is unresponsive to HLA-G-mediated immunosuppressive signals originating from the fetus in these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…, 2014 ; Sotnikova et al , 2014 ; Wang et al. , 2014 ; Almasry et al , 2015 ; Eskicioğlu et al , 2016 ; Radović Janošević et al , 2016 ; Chen et al , 2017 ; Kuon et al , 2017b ; El-Azzamy et al , 2018 ; Liu et al , 2019 ; Marron and Harrity 2019 ; Wei et al ., 2020 ; Lyzikova et al 2020 ; Zhao et al , 2020 ), nine studies on CD56+CD16− cells ( Lachapelle et al. , 1996 ; Yamamoto et al.…”
Section: Resultsunclassified
“…, 2014 ; Sotnikova et al , 2014 ; Wang et al. , 2014 ; Almasry et al , 2015 ; Eskicioğlu et al , 2016 ; Radović Janošević et al , 2016 ; Chen et al , 2017 ; Kuon et al , 2017b ; El-Azzamy et al , 2018 ; Liu et al , 2019 ; Marron and Harrity 2019 ; Wei et al ., 2020 ; Lyzikova et al 2020 ; Zhao et al , 2020 ), nine studies on CD56+CD16− cells ( Lachapelle et al. , 1996 ; Yamamoto et al.…”
Section: Resultsunclassified
“…31 However, the results of some other studies are not consistent with this study. 32 Bhalla and colleagues evaluated the expression of HLA-G using immunohistochemistry staining in placental tissue of the subjects with RM samples compared with the healthy control group. The results showed that the rate of HLA-G expression is not significantly different between 2 groups.…”
Section: Resultsmentioning
confidence: 99%
“…A null mutation that results in no functional HLA-G1 or G5 protein isoforms has been associated with increased risk of recurrent miscarriage (Aldrich et al , 2001; Pfeiffer et al , 2001); HLA-G 725 promoter polymorphism is a risk factor for recurrent miscarriages. In the same line, Eskicioğlu et al (2016) encountered a significant increase in TNF expression in patients with recurrent miscarriages, (Eskicioğlu et al , 2016), and consequently increased cytotoxic activity in the maternal immune system that explained the miscarriages. In these patients, even with no change in HLA-G expression, the maternal immune system is unresponsive to HLA-G immunosuppressive signals from the embryo and fetus.…”
Section: Discussionmentioning
confidence: 94%